PENYUSUNAN BASIS DATA GEOSPASIAL KELURAHAN MELALUI PENDEKATAN PEMETAAN PARTISIPATIF DI KOTA KENDARI - Ido, Irfan; Analuddin, Analuddin; Syaf, Hasbullah; Muliddin, Muliddin; Yunus, Lukman; Mukminin, Ansyahrul (Universitas Halu Oleo, 2023)
The purpose of this writing is to share knowledge about Construction of A Neighborhood Geospatial Data Base Through A Participatory Mapping Approach In Kendari City. The method uses the survey and learning by doing method, namely conveying information accompanied by discussion, questions and answers and examples of applications. The result of this activity is the implementation of community service activities for Participatory Mapping in the Context of Preparing a Geospatial Database in Bende Subdistrict, namely (a) increasing knowledge of subdistrict officials and the community regarding geospatial theory and databases as well as participatory mapping and spatially based slum area database grouping; (b) increasing knowledge about basic technical skills for preparing sub-district administrative maps and slum area maps using geospatial data approaches and participatory mapping approaches; (c) Joint agreement in determining the administrative area boundaries of the Bende Subdistrict RT/RW as the basis for preparing the subdistrict administrative map; (d) Joint agreement in determining slum areas in Bende Village; and (e) Preparation of sub-district administration maps and maps of Bende Sub-district slum areas.